(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2026)
Quantum mechanics is empirically unmatched, yet its ontology remains unsettled. This paper advances a realist research program that treats wave–particle duality as a deep source of several tensions in quantum foundations, including measurement, localization, and wave–function collapse. It further argues that these issues are often intensified by hypostatization: the elevation of abstract elements of the formalism, especially the wave function, to the status of concrete physical entities without clear criteria for physical reality. To address this, the paper develops physical realism, a realist framework that regulates ontological commitment by explicit anti–hypostatization criteria. On that basis, it proposes an energistic ontology for quantum foundations at the quantum level. This gives rise to the hypothesis of a Universal Energy Field (UEF) and energy wave–forms as alternatives to the dualistic wave-particle framework. Although its main emphasis is on ontology, the paper introduces also an initial formal description of energistic dynamics in Appendix A. Its role is primarily to show that the paper’s main conceptual claims can be mathematically tractable, with the UEF and energy wave–forms being expressed through primitive postulates, an initial regime–dependent dynamics, and a stationary condensation equation.